2020
DOI: 10.1155/2020/1472514
|View full text |Cite
|
Sign up to set email alerts
|

Comparing High-Intensity Interval Training (HIIT) and Continuous Training on Apelin, APJ, NO, and Cardiotrophin-1 in Cardiac Tissue of Diabetic Rats

Abstract: Background and Aims. Exercise activity is an important method for managing type 2 diabetes. This investigation examined the HIIT and continuous training on apelin, APJ receptor, NO, and cardiotrophin-1 in the cardiac tissue of diabetic rats. Methods. The animals were categorized into 3 groups of HIIT, continuous (CO), and control (C) (all animals were sacrificed immediately and 2 days after exercise training period). Rats underwent the treadmill exercise program either HIIT (12 bouts at 90–95% of VO2 max with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…Kon et al [35] depicted that the sprint interval training increased the apelin levels in healthy men. Sabouri et al [36] exhibited through the animal study that exercise increased the apelin levels, regardless of exercise type. Krist et al [37] and Sheibani et al [38] reported that the exercise training diminished the apelin value and apelin mRNA in plasma and fat tissue, respectively, in obese individuals and impaired the glucose-tolerant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kon et al [35] depicted that the sprint interval training increased the apelin levels in healthy men. Sabouri et al [36] exhibited through the animal study that exercise increased the apelin levels, regardless of exercise type. Krist et al [37] and Sheibani et al [38] reported that the exercise training diminished the apelin value and apelin mRNA in plasma and fat tissue, respectively, in obese individuals and impaired the glucose-tolerant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Al respecto, no existe información sobre el efecto del ejercicio en los niveles plasmáticos de CT1 en humanos. En rata se ha descrito que el ejercicio incrementa los niveles de CT1 en el corazón, y este aumento es mayor a mayor intensidad del ejercicio 30 . Sin embargo, también en rata, se ha descrito que los niveles plasmáticos de CT1 disminuyen al realizar ejercicio en treadmill y al nadar 31 .…”
Section: Ct-1 En Clínica Y En Modelos Experimentalesunclassified
“…However, the effect of apelin on diabetic nephropathy is currently controversial. A previous study has reported that the levels of apelin/APJ in the serum of patients with diabetic nephropathy are elevated, promoting the occurrence and development of diabetic nephropathy ( 17 ). On the other hand, a different study revealed that apelin-13 could inhibit the morphological changes of renal tubular epithelial cells in the high-glucose environment, thereby inhibiting the occurrence and development of the epithelial-mesenchymal transition (EMT) process in glomerular cells, and ultimately delaying the occurrence of diabetic nephropathy ( 18 ).…”
Section: Introductionmentioning
confidence: 99%